OMOIYARI AS THE BASIS FOR PROSOSIAL BEHAVIOUR IN JAPANESE CHILDREN’S FOLKTALE: OMOIYARI SEBAGAI DASAR PERILAKU PROSOSIAL DALAM CERITA ANAK JEPANG - Linda Unsriana; Alfredo Sotaroma Zendrato (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
Omoiyari is an understanding of how to think about other people's feelings. With that understanding, it will lead us to think about what to do or what not to do to others. As many as 61.9% of parents in Japan want their children to have an omoiyari attitude. This shows how important it is in Japanese society. This study is to find out how the application of the omoiyari concept and its relation to prosocial behavior. The corpus of data to be studied is the folktale of Japanese children, considering that one of the functions of folktales is to instill moral teachings. The method used in this research is a qualitative method, with a literature study method. There are five tales that will be used in this study, namely the Kasa Jizou (Budha Statue), Shita kiri Suzume, Urashima Taro, Hanasaki Jiisan and Tsuru no Ongaeshi. From the data analysis, it is found that the tales describe the omoiyari concept of each of the main characters, as well as the protagonist's prosocial behavior towards other people or creatures.